Papers and Notes Presented to the Institute from July 1943 to February 1969 (The Southern African Institute of Mining and Metallurgy)
YEAR 1943-1944 Vol. 44 Page A major change-over in the ventilation of a deep level mine, by F. G. Hill and E. C. Ranson, 27; Discussion 56, 62, 67, 71, 72, 79, 123, 129 131 A note on the quarrying of surface limestone in the Sinai Desert, by V. L. Bosazza.. .. 59 Mining with diamond drills at the Nkana Mine of the Rhokana Corporation, Limited, Northern Rhodesia, by W. A. Odgers and A. G. Stirling, 95; Discussion 117, 121, 122 123 On silicates and dusts from the Witwatersrand gold mines (some preliminary notes), by J. J. Frankel, 169; Discussion .. 178 Presidential Address-Review of the rock pressure problem, by C. Biccard Jeppe, 3; Discussion 11,15 17 The chemistry, production and application of plastics, by P. N. Lategan, 138; Discussion 151 153 YEAR 1944-1945 Vol. 45 Page A microtechnique for the size-grading of mine dust, by S. R. Rabson, 34; Discussion 49, 50, 52 55 Activated carbon for regenerating used lubricating oil, by F. J. Tromp and J. J. Matthee 90 A contribution to the study of the production of zeolites, by C. C. le Grange and A. J. Petrick 235 A laboratory method for the determination of the suitability of South African coal and coal blends for the manufacture of metallurgical coke, by R. F. J. Teichmann .. .. 202 Copper containing cements for self-sanitising surfaces, by R. S. Young and H. L. Talbot 156 Notes on some sulphide minerals from the Far East Rand, by E. Mendelssohn, 84; Discussion, 88 89 Presidential Address-A review of underground support on the Witwatersrand with its Bearing on the Problem of ultradeep mining, by P. J. Louis Bok, 3; Discussion, 24, 25 27 Scientific management with particular application to a Witwatersrand gold mine, by J. S. Ford, 63; Discussion, 77, 80, 82 83 Some aspects of rock-drilling practice (the Witwatersrand gold field), by C. J. Irving, 163; Discussion, 185, 190 *197 Temperature measurements in a mine on the Witwatersrand with an electrical resistance thermometer, by O. Weiss, 127; Discussion, 136 137 The measurement of the geo-thermic gradient by means of the clinical thermometer, by R. A. H. Flugge-de Smidt, 105; Discussion, 136 137 The micro-chemical determination of free and combined silica in mine dust, by S. R. Rabson, 43; Discussion, 49, 50, 52 55 The oxidation of pyrites associated with South African coals, by R. F. J. Teichmann 141 YEAR 1945-1946 Vol. 46 Page Air cooling plant, No. 4 Shaft, City Deep, Limited. A review of layout and results achieved, by H. W. Unwin, A. Malcolm and R. E. Campbell Pitt, 66; Discussion, 100, 102, 103, 106, 110 115 A preliminary note on the Waterberg coal field as a possible source of coking coal, by P. E. Hall 124